Emergency management of immune-related toxicity. Issue 4 (July 2020) - Cooksley, Tim; Stutman, Robin; Klotz, Adam
Abstract : Purpose of review: Emergency presentations in patients treated with immune checkpoint inhibitors (ICIs) are a clinical challenge. Clinicians need to be vigilant in diagnosing and treating immune-mediated toxicities. In this review, we consider the approach to managing an acutely unwell patient being treated with ICIs presenting as an emergency. Recent findings: A minority of acutely unwell patients treated with ICIs will have an immune-mediated toxicity. Early recognition and intervention in those with immune-mediated toxicity can reduce the duration and severity of the complications. The use of early immunosuppressive agents along corticosteroid therapy may improve outcomes in patients with life-threatening immune-mediated toxicity. Summary: Individualized management of immune-mediated toxicities is a key challenge for emergency oncology services; this has become part of routine cancer care.